Prognostic value of admission high-sensitivity troponin in patients with ST-elevation myocardial infarction. Issue 23 (20th September 2021) - Coelho-Lima, Jose; Georgiopoulos, Georgios; Ahmed, Javed; Adil, Syeda E R; Gaskin, David; Bakogiannis, Constantinos; Sopova, Kateryna; Ahmed, Fareen; Ahmed, Haaris; Spray, Luke; Richardson, Gavin; Bagnall, Alan J; et al.
Abstract : Background and aim: Although the diagnostic usefulness of high-sensitivity cardiac troponin T (hs-cTnT) is well established in ST-segment elevation myocardial infarction (STEMI), its prognostic relevance in risk stratification of patients with STEMI remains obscure. This study sought to determine the prognostic value of pre-reperfusion (admission) and post-reperfusion (12-hour) hs-cTnT in patients with STEMI treated with primary percutaneous coronary intervention (PPCI). Methods: Retrospective observational longitudinal study including consecutive patients with STEMI treated with PPCI at a university hospital in the northeast of England. hs-cTnT was measured at admission to the catheterisation laboratory and 12 hours after PPCI. Clinical, procedural and laboratory data were prospectively collected during patient hospitalisation (June 2010–December 2014). Mortality data were obtained from the UK Office of National Statistics. The study endpoints were in-hospital and overall mortality. Results: A total of 3113 patients were included. Median follow-up was 53 months. Admission hs-cTnT >515 ng/L (fourth quartile) was independently associated with in-hospital mortality (HR=2.53 per highest to lower quartiles; 95% CI: 1.32 to 4.85; p=0.005) after multivariable adjustment for a clinical model of mortality prediction. Likewise, admission hs-cTnT >515 ng/L independently predicted overall mortality (HR=1.27 per highest to lower quartiles; 95% CI: 1.02 to 1.59; p=0.029). Admission hs-cTnT correctly reclassified risk for in-hospital death (net reclassification index (NRI)=0.588, p<0.001) and overall mortality (NRI=0.178, p=0.001). Conversely, 12-hour hs-cTnT was not independently associated with mortality. Conclusion: Admission, but not 12-hour post-reperfusion, hs-cTnT predicts mortality and improves risk stratification in the PPCI era. These results support a prognostic role for admission hs-cTnT while challenge the cost-effectiveness of routine 12-hour hs-cTnT measurements in patients with STEMI.